Medicine Storage Knowledge Survey among Pharmacy Students from Universitas Gadjah Mada - Lovendri, Dolorosa Septin; Kristina, Susi Ari (Academic Hospital Journal, 2023)
Proper drug storage is very important to ensure drug safety, quality and efficacy. Drug storage is closely related to drug expiration which includes Expiry Date (ED) and Beyond Use Date (BUD). The aim of this research was to measure the level of knowledge of Pharmacy students at Gadjah Mada University regarding drug storage and drug expiration. This research uses a designcross-sectional study with an instrument in the form of a questionnaire. The sample was UGM Pharmacy Students taken randomlyconvenience sampling, in the data collection period October-November 2023, there were 132 respondents. A questionnaire covering sociodemographic data, storage domains and drug expiration time, was distributedgoogleform. Data were analyzed descriptively and with statistical testsChi-square with p<0.05. The results of the study showed that 87.88% (N= 116) of UGM Pharmacy Students had a good level of knowledge about drug storage, and 85.85% (N= 112) had a poor level of knowledge about drug expiration. There was no relationship between gender (p=0.307); age (p=0.639); semester (p=0.791); monthly income (p=0.897); parents' field of work (p=0.155); and current state of residence (p=0.904) with knowledge of drug storage. There is a relationship between age (p value 0.012); semester (p=0.015); and current state of residence (p=0.019) with knowledge of drug expiration. It is necessary to increase pharmacy students' literacy about drug expiration to ensure drug safety.